The use of correspondence analysis in the study of foreign divestment in the Visegrad Countries during the coronavirus crisis - Salamaga, Marcin (Zastosowanie analizy korespondencji do badania ryzyka dezinwestycji zagranicznych w czasie koronakryzysu w krajach Grupy Wyszehradzkiej, 2021)
The deterioration of the general investment climate, the economic recession, and changes in consumption patterns caused by the COVID-19 pandemic have forced various foreign investors to restrict or suspend investments. One of the possible reactions by investors to the coronavirus crisis is divestment. This article aimed at detecting and analysing the regularities between the risk of foreign divestment in various industry branches and the destinations of FDIs at the level of NUTS 1 macroregions of the Visegrad Group countries during the COVID-19 pandemic, using correspondence analysis. The results of the assessment of the risk of foreign divestment in NUTS 1 macroregions of the Visegrad Group countries are characterised by diversity in terms of territorial and sectoral layout, depending on the analysed scenario of the COVID-19 pandemic development. It is hard to clearly indicate a macroregion which, irrespective of the scale of the spread of the disease, could be perceived by foreign investors as invariably highly risky or characterised by a constantly low risk of divestment
Econometrics = Ekonometria, 2021, Vol. 25, No. 2, s. 15-26
Keywords: correspondence analysis; questionnaire survey; foreign destinations; COVID-19; analiza korespondencji; badania ankietowe; bezpośrednie inwestycje zagraniczne; destynacje zagraniczne